Insights into the roles of macrophages in Klebsiella pneumoniae infections: a comprehensive review - Yangguang Li; Xuanheng Li; Wenqi Wu; Peizhao Liu; Juanhan Liu; Haiyang Jiang; Liting Deng; Chujun Ni; Xiuwen Wu; Yun Zhao; Jianan Ren (Cellular & Molecular Biology Letters)
Abstract Klebsiella pneumoniae (KP) infections represent a significant global health challenge, characterized by severe inflammatory sequelae and escalating antimicrobial resistance. This comprehensive review elucidates the complex interplay between macrophages and KP, encompassing pathogen recognition mechanisms, macrophage activation states, cellular death pathways, and emerging immunotherapeutic strategies. We critically analyze current literature on macrophage pattern recognition receptor engagement with KP-associated molecular patterns. The review examines the spectrum of macrophage responses to KP infection, including classical M1 polarization and the newly described M(Kp) phenotype, alongside metabolic reprogramming events such as glycolytic enhancement and immune responsive gene 1 (IRG1)–itaconate upregulation. We systematically evaluate macrophage fate decisions in response to KP, including autophagy, apoptosis, pyroptosis, and necroptosis. Furthermore, we provide a critical assessment of potential future therapeutic modalities. Given the limitations of current treatment paradigms, elucidating macrophage–KP interactions is imperative. Insights gained from this analysis may inform the development of novel immunomodulatory approaches to augment conventional antimicrobial therapies, potentially transforming the clinical management of KP infections. Graphical Abstract